2022
DOI: 10.1093/biolinnean/blab165
|View full text |Cite
|
Sign up to set email alerts
|

Distance to coastline modulates morphology and population structure in a coastal amphibian

Abstract: Salinization due to sea-level rise and marine submersions is expected to strongly impact coastal ecosystems. Exposure to salinity can negatively impact biodiversity especially in coastal wetlands. To understand comprehensively the consequences of environmental salinization on coastal biodiversity, it is essential to document how coastal species currently respond to exposure to salinity. In this study, we investigated how variations of environmental salinity relative to the distance to the ocean influence popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 62 publications
3
27
0
Order By: Relevance
“…Our study species can be found in ponds in which the salinity (ranging from 0 to 16 g L −1 ) is similar to those experienced by other species found in coastal marshes ( Hopkins and Brodie, 2015 ). The salinity experienced in the field (0–7 g L −1 ) was correlated with physiological parameters (osmolality, monocytes and eosinophils counts), negatively correlated with body condition and locomotor performance and seems to influence size- and sex-specific habitat selection (see also Lorrain-Soligon et al, 2022b ). Experimentally, we demonstrated that short-term exposure to environmental salinity significantly affects physiological parameters [salt influxes (osmolality), water effluxes (body mass), immunity (leukocyte counts)] and locomotor performance (jumping distances and activity).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study species can be found in ponds in which the salinity (ranging from 0 to 16 g L −1 ) is similar to those experienced by other species found in coastal marshes ( Hopkins and Brodie, 2015 ). The salinity experienced in the field (0–7 g L −1 ) was correlated with physiological parameters (osmolality, monocytes and eosinophils counts), negatively correlated with body condition and locomotor performance and seems to influence size- and sex-specific habitat selection (see also Lorrain-Soligon et al, 2022b ). Experimentally, we demonstrated that short-term exposure to environmental salinity significantly affects physiological parameters [salt influxes (osmolality), water effluxes (body mass), immunity (leukocyte counts)] and locomotor performance (jumping distances and activity).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adult females mobilize large amount of energy to reproduce ( Wells, 2007 ; Hayward and Gillooly, 2011 ) and energetic constraints of life in brackish water (either directly linked to osmoregulation, or indirectly linked to foraging efficiency, see above) may negatively interact with the energetic requirements of reproduction. Complementarily, such a biased sex-ratio may also be linked to habitat selection processes for which amphibian females have been shown to select less brackish sites to mate and lay their eggs in order to decrease the negative consequences of elevated salinity on embryonic and larval development ( Haramura, 2008 ; Albecker and McCoy, 2017 ; Lorrain-Soligon et al, 2022b ). It is noteworthy that we focused our investigation on pond salinity and we did not assess other parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, these patterns may reveal trade‐offs linked to adaptive processes. Indeed, coastal anurans may have evolved specific physiological adaptations to promote life in hyperosmotic environments (Albecker & McCoy, 2019; Gomez‐Mestre & Tejedo, 2003; Hopkins et al, 2016), notably through mechanisms that allow them to reduce salt intake (or increase excess salt excretion) and/or to increase water influxes (or reduce water effluxes, Lorrain‐Soligon, Bichet, et al, 2022; Lorrain‐Soligon, Robin, et al, 2022). In turn, these mechanisms may become maladaptive in hyposmotic water bodies because of elevated salt loss and excessive water influxes (Lorrain‐Soligon, Bichet, et al, 2022), leading to massive oedema and mortality (L. Lorrain‐Soligon, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most amphibians are characterised by a complex biphasic life cycle, with eggs and tadpoles developing in aquatic habitats and adults displaying various levels of terrestriality (Wells, 2007). Accordingly, eggs and larvae are less tolerant to elevated salinity than adults (Albecker & McCoy, 2017), and some evidence suggest that reproductive individuals can express habitat selection and avoid saline water for egg‐laying (Albecker & McCoy, 2017; Haramura, 2008; Lorrain‐Soligon, Robin, et al, 2022; Viertel, 1999) to improve their reproductive success (Lukens & Wilcoxen, 2020; Tornabene et al, 2021). Taken together, these elements suggest that variability in both within‐ and between‐species susceptibility to salinity could be a major factor determining the structure of amphibian coastal communities (Lorrain‐Soligon et al, 2021) and may significantly affect within‐ and between‐species distribution across the spatial and temporal salinity gradient.…”
Section: Introductionmentioning
confidence: 99%